Partisipasi Manajemen Memoderasi Optimalisasi Teknologi Informasi Pada Efektivitas Sistem Informasi Akuntansi - Putu Diah Kumalasari; Ni Luh Putu Widhiastuti; Ni Luh Putu Sandrya Dewi (Jurnal Akuntansi Terapan dan Bisnis, 2023)
This study aims to determine the role of management participation in moderating the influence of the use of information technology on the effectiveness of the Accounting Information System (AIS). The sample in this study was 110 people who were Lembaga Perkreditan Desa’s (LPD) employees in Sukawati District, determined by purposive sampling method. The analysis technique used is Multivariate Regression Analysis (MRA). The results showed that management participation was able to moderate the influence of information technology optimization on the effectiveness of the AIS. This proves the important role of management in carrying out the supervisory function and developing the AIS so that information technology can be utilized optimally.